The Role of Accuracy and Comprehensiveness of Information in Improving Strategic Decisions A Field Study at Tishreen University"" - بهلول ذو الفقار; حنان تركمان; لينا فياض (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to study the relationship between accuracy and comprehensiveness of information as dimensions of information quality and strategic decision at Tishreen University, where reliance was placed on two dimensions of information quality: (accuracy and comprehensiveness). The researcher relied on the descriptive analytical approach to describe the variables of the study, where the questionnaire was used as a tool to collect primary data by distributing it to a simple random sample of workers at Tishreen University, which amounted to (460) questionnaires. (420) questionnaires were retrieved, and it was suitable for analysis (384) and for testing. Hypotheses: The researcher used the Student T test for one sample, as well as the Pearson correlation coefficient. The research found that there was an increase in the level of information accuracy, as well as a decrease in the level of both comprehensiveness of information and the level of strategic decision at Tishreen University. The results also showed a significant relationship between the dimensions of information quality (accuracy and comprehensiveness) and strategic decision; therefore, there is a significant role for the accuracy and comprehensiveness of information in improving the strategic decision of university employees. The research presented a set of recommendations and proposals related to the need to improve the strategic decision-making process by having clear criteria for choosing the best alternatives, improving the level of accuracy and comprehensiveness of information among employees by setting standards that ensure obtaining the required quality and quantity of information necessary to improve the university’s strategic decision.